Absorptive capacity and innovation: an analysis of business management of young entrepreneurs - Werlang, Bruna Luisa; Werlang, Nathalia Berger (Revista de Administração da UFSM, 2021)
Purpose – The current study has the objective to understand how young entrepreneurs develop absorptive capacity and innovation from the processes of acquisition, assimilation, transformation and knowledge application acquired from external sources. Design/methodology/approach – The research is identified as theoretical-empirical, with qualitative basis, descriptive, through a field research operationalized with a multiple case study. The survey sample consists of 07 companies run by young entrepreneurs. Data analysis occurred through content analysis. Findings – As main results, some relevant practices were evidenced for each dimension of absorptive capacity. For acquisition, the exchange and search for information, the importance of networking, and participation in events and fairs stand out. Knowledge assimilation happens from holding meetings, incentives in training and opinion formation. Knowledge transformation is accomplished from the structuring and new sources of knowledge. Lastly, knowledge application occurs through the creation of innovative products and services, technological advantages and strategies. Research limitations/implications - The present study has as a limitation the sample size, which may have a bias in the result from the viewpoint of the participants. Originality/value – As main contributions, the study presents how the absorptive capacity process of young entrepreneurs takes place and the main actions and practices carried out by them in the management of their own businesses.